STUDY AND ANALYSIS OF GRAPHS AND MODELS BASED INTERCONNECTION NETWORK SYSTEM - Gupta, Raj Kumar; Jaiswal, K.L. (International Journal of Engineering Technologies and Management Research, 2021)
The topology of network connections has become a vital step in the implementation of all conventional network networks. Cube architecture is one of the key aspects of network integration that explore and create networks of cubes. They praise and work together to complete all network management tasks. However, in this article, we will focus on the error handling function.